SP2DK sebagai sarana komunikasi antara Wajib Pajak dan Fiskus - Suryani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
Purpose: This study aims to explain that SP2DK is an important part of tax administration supervision efforts that provides taxpayers with the opportunity to explain and make corrections if necessary. Research Design and Methodology: The author began the identification process related to SP2DK by selecting relevant tax journals and books on cases and fields of knowledge that included several articles and research in Indonesia. Findings and Discussion: Main Objectives of SP2DK: (1) Early Supervision Tool: SP2DK functions as the earliest supervisory effort which is preventive and persuasive in nature. (2) Encouraging Voluntary Compliance: Encouraging Taxpayers to conduct a re-evaluation (self-review) of the Tax Return (SPT) that has been submitted and, if necessary, make corrections to the SPT and pay off the remaining tax payments owed. (3) Testing Material Compliance: This clarification aims to test the material accuracy of SPT reporting, for example through data equalization between the Taxpayer's financial report and third-party data held by the tax authorities. Implications: This study emphasizes the need for SP2DK is an important part of tax administration supervision efforts that provides opportunities for Taxpayers.